2008
DOI: 10.1007/s11627-008-9134-1
|View full text |Cite
|
Sign up to set email alerts
|

Podophyllotoxin production via cell and adventitious root cultures of Podophyllum peltatum

Abstract: Podophyllum peltatum is an important medicinal plant that produces podophyllotoxin (PTOX) with anticancer properties. We established the embryogenic cell and adventitious root culture systems in P. peltatum and analyzed PTOX production. For the growth of embryogenic cell clumps in shake flask culture, the most efficient concentration of 2,4-dichloroacetic acid (2,4-D) was 6.78 μM, and the growth of embryogenic cell clumps was 15.9-fold increased in Murashige and Skoog MS liquid medium with 6.78 μM 2,4-D after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 22 publications
(23 reference statements)
1
23
0
Order By: Relevance
“…After equal culture times (8 weeks), the podophyllotoxin content was significantly higher in the cultured rhizome (3.20 mg g -1 ) than in the calli (1.17 mg g -1 ). Similar results were achieved for P. peltatum (Anbazhagan et al 2008). They found that podophyllotoxin content in embryogenic cells (coming from embryogenic callus) was 0.0865 mg g -1 , and 0.362 mg g -1 in adventitious roots.…”
Section: Podophyllotoxin Contentsupporting
confidence: 79%
See 1 more Smart Citation
“…After equal culture times (8 weeks), the podophyllotoxin content was significantly higher in the cultured rhizome (3.20 mg g -1 ) than in the calli (1.17 mg g -1 ). Similar results were achieved for P. peltatum (Anbazhagan et al 2008). They found that podophyllotoxin content in embryogenic cells (coming from embryogenic callus) was 0.0865 mg g -1 , and 0.362 mg g -1 in adventitious roots.…”
Section: Podophyllotoxin Contentsupporting
confidence: 79%
“…In addition, they found that phenylalanine (0.2 g l -1 ) enhanced the production of podophyllotoxin in calli to 5 mg g -1 . Anbazhagan et al (2008) showed that elicitor treatment (20 lM methyl jasmonate) strongly enhanced the production of podophyllotoxin in both embryogenic cell clumps and adventitious roots. In our study, the podophyllotoxin content in the calli growing for 8 weeks reached one-fifth of that in wild plants that had grown for 2 years.…”
Section: Podophyllotoxin Contentmentioning
confidence: 99%
“…Jasmonates are signal molecules and plant regulators that mediate various developmental processes and induce plant defense responses to pathogens and insects (Chen et al, 2007;Yu et al, 2002;Rhee et al, 2010). In particular, exogenous application of MJ as an elicitor can be effective to stimulate the production of various secondary metabolites belonging to different structural groups in plant cell and tissue cultures (Yoo et al, 2011;Zhao et al, 2010;Rhee et al, 2010), including the formation of decursinol angelate in A. gigas root culture (Rhee et al, 2010), ginsenosides in Panax ginseng hairy root and adventitious root culture (Yu et al, 2002;Hong et al, 2012), podophyllotoxin in Podophyllum peltatum adventitious root and cell cultures (Anbazhagan et al, 2008), saikosaponins in Bupleurum kaoi adventitious root culture (Chen et al, 2007) and hyoscyamine and scopolamine in A. belladonna hairy root culture (Eskandari et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…One of these sources is the rhizomes of the plant Podophyllum peltatum [6]. Due to a combination of the slow growth-rate of the plant and increasing demand for PPT [7][8][9], various other approaches for the chemical synthesis and in vitro production of PPT have been explored [1,[10][11][12][13][14]. These methods have so far proven to be inadequate for the commercial production of PPT due to low yields and high costs.…”
Section: Introductionmentioning
confidence: 99%